2022
DOI: 10.3389/fphar.2022.950337
|View full text |Cite
|
Sign up to set email alerts
|

A review on therapeutical potential of paeonol in atherosclerosis

Abstract: The morbidity and mortality of atherosclerotic cardiovascular disease (ASCVD) is increasing year by year. Cortex Moutan is a traditional Chinese medicinal herb that has been widely used for thousands of years to treat a wide variety of diseases in Eastern countries due to its heat-clearing and detoxifying effects. Paeonol is a bioactive monomer extracted from Cortex Moutan, which has anti-atherosclerotic effects. In this article, we reviewed the pharmacological effects of paeonol against experimental atheroscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 165 publications
0
8
0
Order By: Relevance
“…For more information on Sect. Moutan, please refer to the reference ( 10 ). Specifically, the PLP first appeared in written records in the earliest Chinese pharmacological work<神农本草经> (Shen nong Ben Cao Jing) in Eastern Han Dynasty, 25-220 AD.…”
Section: Paeoniflorinmentioning
confidence: 99%
See 1 more Smart Citation
“…For more information on Sect. Moutan, please refer to the reference ( 10 ). Specifically, the PLP first appeared in written records in the earliest Chinese pharmacological work<神农本草经> (Shen nong Ben Cao Jing) in Eastern Han Dynasty, 25-220 AD.…”
Section: Paeoniflorinmentioning
confidence: 99%
“…The discovery of new drugs from natural products has become a new approach to discovering the treatment of CVD including atherosclerosis. Some extracts or single units of natural drugs have shown enormous potential for the therapy of atherosclerosis, such as paeonol ( 10 ). As an ornamental and medicinal plant widely distributed around the world, P. lactiflora is receiving increasing attention in the research and development of natural drugs.…”
Section: Introductionmentioning
confidence: 99%
“…[15] MC possesses a range of pharmacological activities, including anticoagulant, anti-inflammatory, anti-tumour, and improvement in diabetes mellitus, among others. [15][16][17][18][19][20] However, MC is less used in agriculture, especially for fungicidal activity. Interestingly, our group discovered in a previous study that MC ethanol extract exhibited fungicidal activity against a wide range of plant pathogenic fungi, especially against R. solani, with 100 % inhibitory activity at a concentration of 1000 μg/mL.…”
Section: Introductionmentioning
confidence: 99%
“…Moutan cortex (MC), derived from the root bark of Paeonia suffruticosa Andrews, has been utilized in China's clinical practice for nearly 2000 years [15] . MC possesses a range of pharmacological activities, including anticoagulant, anti–inflammatory, anti–tumour, and improvement in diabetes mellitus, among others [15–20] . However, MC is less used in agriculture, especially for fungicidal activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, Guizhi Fuling Decoction, as a classical formula, has complex and unclear composition. Paeonol in Guizhi Fuling Decoction was found to improve disease by regulating inflammation, platelet aggregation, lipid metabolism, mitochondrial damage, and endoplasmic reticulum autophagy [ 20 , 21 ]. Peng Yi et al investigated the mechanism by which paeonol alleviates dysmenorrhea in mice and found that paeonol reduces inflammatory cytokines and simultaneously inhibits uterine contractions [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%